More Than the Usual Turmoil: The 2019 Provincial Election in Newfoundland and Labrador - Loder, Hannah; Marland, Alex (c/o Institute for Governance Studies, Simon Fraser University, 2021)
Turmoil in the House of Assembly leading up to the 2019 general election in Newfoundland and Labrador foreshadowed an unusual result. Liberal Premier Dwight Ball, stung by public outrage over his government’s 2016 austerity budget, spent the balance of his term wary of difficult decisions while ministers and MHAs hurled accusations of bullying at each other. The Liberal government routinely evoked its The Way Forward planning document as a source of policy solutions and blamed the Progressive Conservatives for sanctioning the Muskrat Falls hydroelectric project boondoggle. Public opinion polls often put the Liberals in front, but Ball’s popularity lagged behind his party’s and occasionally that of the opposition leaders. The election produced the first minority government in nearly half a century, including the rare victory of two Independents, and the Liberal caucus soon agitated for new leadership. The province’s dire economic circumstances mean that more political turmoil is likely.RésuméLes turbulences à l’assemblée législative à l'approche des élections générales de 2019 à Terre-Neuve-et-Labrador laissent présager un résultat inhabituel. Le premier ministre libéral Dwight Ball, piqué par l'indignation de la population à propos du budget d'austérité de son gouvernement pour 2016, a passé le reste de son mandat à se méfier des décisions difficiles, tandis que les ministres et les députés se lançaient des accusations d'intimidation les uns envers les autres. Le gouvernement libéral a régulièrement évoqué son document de planification «The Way Forward» comme une source de solutions politiques et a reproché aux progressistes-conservateurs d'avoir sanctionné le gâchis du projet hydroélectrique de Muskrat Falls. Les sondages d'opinion mettent souvent les libéraux en avance, mais la popularité de Ball est à la traîne par rapport à celle de son parti et, parfois, des chefs de l'opposition. L'élection a produit le premier gouvernement minoritaire en près d'un demi-siècle, y compris la rare victoire de deux ...